Discovery and functional prioritization of Parkinson's disease candidate genes from large-scale whole exome sequencing. Issue 1 (December 2017) - Jansen, Iris; Ye, Hui; Heetveld, Sasja; Lechler, Marie; Michels, Helen; Seinstra, Renée; Lubbe, Steven; Drouet, Valérie; Lesage, Suzanne; Majounie, Elisa; Gibbs, J.; Nalls, Mike; et al.
Abstract Background Whole-exome sequencing (WES) has been successful in identifying genes that cause familial Parkinson's disease (PD). However, until now this approach has not been deployed to study large cohorts of unrelated participants. To discover rare PD susceptibility variants, we performed WES in 1148 unrelated cases and 503 control participants. Candidate genes were subsequently validated for functions relevant to PD based on parallel RNA-interference (RNAi) screens in human cell culture andDrosophila andC. elegans models. Results Assuming autosomal recessive inheritance, we identify 27 genes that have homozygous or compound heterozygous loss-of-function variants in PD cases. Definitive replication and confirmation of these findings were hindered by potential heterogeneity and by the rarity of the implicated alleles. We therefore looked for potential genetic interactions with established PD mechanisms. Following RNAi-mediated knockdown, 15 of the genes modulated mitochondrial dynamics in human neuronal cultures and four candidates enhanced α-synuclein-induced neurodegeneration inDrosophila . Based on complementary analyses in independent human datasets, five functionally validated genes—GPATCH2L, UHRF1BP1L, PTPRH, ARSB, andVPS13C —also showed evidence consistent with genetic replication. Conclusions By integrating human genetic and functional evidence, we identify several PD susceptibility gene candidates for further investigation. Our approach highlights a powerful experimental strategy with broad applicability for future studies of disorders with complex genetic etiologies.